The effects of social mindfulness and online interpersonal trust on college students’ online prosocial behavior - Hao, Jiajia; Liu, Yinuo; Ma, Xinran; Gong, Shimiao (Frontiers in Psychiatry, 2025)
IntroductionWith the widespread adoption of the internet and social media, adolescents’ social interactions through online platforms have increasingly expanded. Adolescents’ prosocial activities in cyberspace not only serve as important indications of their socialization but also show how the internet and technology impact the new generation’s psychological adjustment and social integration patterns. Our study aimed to construct a moderated mediation model to explore the impact of social mindfulness on online prosocial behavior, as well as the mediating role of perceived prosocial impact and the moderating role of online interpersonal trust. Three experiments were designed based on the model to verify the applicability of the previously constructed model in real-world contexts.MethodsIn Study 1, a cross-sectional study was conducted at a college in China, recruiting 328 college students using self-report questionnaires. The Social Mindfulness Self-Report Scale, the Online Prosocial Behavior Extension Scale (Chinese Version), the Perceived Social Impact Scale, and the Online Interpersonal Trust Scale were used. This study explored the relationship between social mindfulness and online prosocial behavior, the mediating effect of perceived prosocial impact, and the moderating role of online interpersonal trust. In Study 2, we adopted experimental research among 60 Chinese college students to explore the prosocial behavior of participants with different levels of social mindfulness in online contexts with varying levels of credibility.Results(1) Social mindfulness positively predicted online prosocial behavior, with perceived prosocial impact serving as a partial mediator. Online interpersonal trust moderated the latter part of the mediation model. (2) Social mindfulness and contextual credibility positively predicted college students’ online prosocial behavior.